Glastonbury Festival 2007: The Socio-Economic Impacts on the Host Community - Rose, Eleanor (2008)
Event tourism, particularly festival tourism, is increasingly becoming a focus for tourism research. There are numerous impacts of festival tourism to the tourism industry and they often have numerous effects upon the host community. This research investigates the economic and social impacts of Glastonbury Festival 2007 on the host community. The research estimates a total economic impact on the immediate and the wider geographical area and gains an insight into the social impacts of the Festival for the local community. The results suggest that the economic impact is extremely significant to the host community and there are numerous extremely positive social benefits. There are few detrimental impacts upon the host community however, more could be done to maximise benefits for the local community.